PENGARUH KOMPENSASI TERHADAP MOTIVASI KERJA KARYAWAN PT IDELIE CEMERLANG - Jeng Sari; Fetty Poerwita Sary (LPPM UNIBI, 2019)
Human resources are company assets in achieving company goals. Work motivation is needed in the process of achieving goals so that the company's role in motivating employees is very necessary. One technique to increase work motivation is compensation. The purpose of this study was to determine the effect of compensation on employee work motivation with the object of research, namely PT Idelie Cemerlang employees. The method used in this study is a quantitative method with data collection techniques through the distribution of questionnaires to 45 employees. The type of analysis used is descriptive and causal with the analysis of the data used is descriptive analysis, simple linear regression, determined coefficient, and hypothesis testing. The results obtained in this study are compensation significantly positive effect on the work motivation of PT Idelie Cemerlang employees. The results of this study should be used as input for PT Idelie Cemerlang through giving awards to outstanding employees in the form of certificates in order to motivate employees to improve the performance produced by employees.